2005
DOI: 10.1073/pnas.0506133102
|View full text |Cite
|
Sign up to set email alerts
|

An essential RNase III insertion editing endonuclease in Trypanosoma brucei

Abstract: RNA editing adds and deletes uridine nucleotides in many preedited mRNAs to create translatable mRNAs in the mitochondria of the parasite Trypanosoma brucei. Kinetoplastid RNA editing protein B3 (KREPB3, formerly TbMP61) is part of the multiprotein complex that catalyzes editing in T. brucei and contains an RNase III motif that suggests nuclease function. Repression of KREPB3 expression, either by RNA interference in procyclic forms (PFs) or by conditional inactivation of an ectopic KREPB3 allele in bloodstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
176
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(183 citation statements)
references
References 45 publications
7
176
0
Order By: Relevance
“…S1 and Table S1). However, they are compositionally and functionally distinct in that each contains a different single RNase III endonuclease with a uniquely associated specific partner protein, and a different editing site cleavage specificity (22)(23)(24)(25)(26)29) (SI Appendix, Fig. S1 and Table S1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S1 and Table S1). However, they are compositionally and functionally distinct in that each contains a different single RNase III endonuclease with a uniquely associated specific partner protein, and a different editing site cleavage specificity (22)(23)(24)(25)(26)29) (SI Appendix, Fig. S1 and Table S1).…”
mentioning
confidence: 99%
“…Editing occurs by rounds of coordinated catalytic steps that require a number of different enzymes: cleavage of the mRNA substrate by endonucleases, addition of Us by 3′ terminal uridylytransferase (TUTase) or removal of Us by U-specific 3′ exonuclease (exoUase) at insertion or deletion editing sites, respectively, and rejoining of mRNA fragments by RNA ligases. The enzymes that catalyze RNA editing in T. brucei are in ∼20S editosome complexes that also contain proteins with no known catalytic functions (16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…It was suggested that MP90 is a U-deletion site-specific endonuclease (which was labeled KREN1 for kinetoplast RNA editing nuclease), and MP61 is a U-insertion site endonuclease (which was labeled KREN2). However, recombinant proteins were enzymatically inactive (18,19).In this study, we provide both indirect and direct evidence for a role of the MP90 L-complex protein in the initial cleavage at preedited mRNA U-deletion editing sites, and we show that a full-round cycle of in vitro U-deletion editing can be reconstituted with just three recombinant proteins: REX1, REL1, and MP90. MP90 has been functionally renamed as RNA editing nuclease 1 (REN1).…”
mentioning
confidence: 83%
“…Carnes et al (19) provided indirect evidence for a role of the MP61 or TbREN2 L-complex protein in cleavage of preedited mRNA at U-insertion sites, but the roles of the MP67 and LC8 (MP44) RNase III L-complex proteins are still uncertain, especially in view of the lack of any phenotype of MP67-downregulated cells. And, of course, the precise topology and stoichiometry of the various L-complex proteins, including the REL1 and REL2 subcomplexes and the internal core L-complex proteins and their interaction with mRNAs and gRNAs (29), remain open questions that are critical for understanding this type of RNA editing in detail (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation